All the News That's Fit to Reprint: Do Investors React to Stale Information? - Tetlock, Paul C. (Review of Financial Studies, 2011)
This article tests whether stock market investors appropriately distinguish between new and old information about firms. I define the staleness of a news story as its textual similarity to the previous ten stories about the same firm. I find that firms' stock returns respond less to stale news. Even so, a firm's return on the day of stale news negatively predicts its return in the following week. Individual investors trade more aggressively on news when news is stale. The subsequent return reversal is significantly larger in stocks with above-average individual investor trading activity. These results are consistent with the idea that individual investors overreact to stale information, leading to temporary movements in firms' stock prices. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.